Taking stock of national climate action for forests: 2021 NYDF Assessment report - Haupt, F.; Manirajah, S.M.; Conway, D.; Duchelle, Amy E.; Matson, E.; Peteru, S.; Pham Thu Thuy; NYDF Assessment Partners (New York Declaration on Forests (NYDF), 2021)
The original aim of Goal 7 of New York Declaration on Forests (NYDF) has been met: the Paris Agreement confirms forests’ pivotal role in the international climate agenda. But at a time when the protection, restoration, and sustainable management of forests have never been more urgent, global forest loss is in a worrying upward trend. It is still too early to assess country’s progress on their commitments under the Paris Agreement because countries will only report the status of NDC implementation few years from now. In the meantime, we take stock of governments' existing domestic efforts and policies, and offer recommendations on what governments can do to accelerate forest-based mitigation outcomes.